What is the role of the neutrophil extracellular traps in the cardiovascular disease burden associated with hemodialysis bioincompatibility? - Cristol, Jean-Paul; Thierry, Alain R.; Bargnoux, Anne-Sophie; Morena-Carrere, Marion; Canaud, Bernard (Frontiers in Medicine, 2023)
Despite significant progresses in dialysis modalities, intermittent renal replacement therapy remains an ‘unphysiological’ treatment that imperfectly corrects uremic disorders and may lead to low-grade chronic inflammation, neutrophil activation and oxidative stress due to repetitive blood/membrane interactions contributing to the ‘remaining uremic syndrome’ and cardiovascular disease burden of hemodialysis patients. Understanding dialysis bioincompatibility pathways remains still a clinical/biochemical challenge. Indeed, surrogate biomarkers of inflammation including CRP could not discriminate between all components involved in these complex pathways. Few examples may serve to illustrate the case. Cytokine release during dialysis sessions may be underestimated due to removal using high-flux dialysis or hemodiafiltration modalities. Complement activation is recognized as a key event of bioincompatibility. However, it appears as an early/transient event with anaphylatoxin level normalization at the end of the session. Complement activation is generally assumed to trigger leukocyte stimulation leading to proinflammatory mediators’ secretion and oxidative burst. Beside being part of the innate immune response involved in eliminating physically and enzymatically microbes, the formation of Neutrophil Extracellular Traps (NETs), known as NETosis, has been recently identified as a major harmful component in a wide range of pathologies associated with inflammation. NETs result from the neutrophil degranulation induced by reactive oxygen species overproduction via NADPH oxidase, and consists in modified chromatin decorated with serine proteases, elastase, bactericidal proteins and myeloperoxidase (MPO) that produces hypochlorite anion. Currently, NETosis remains poorly investigated as a sensitive and integrated marker of bioincompatibility in dialysis. Only scarce data could be found in the literature. Oxidative burst and NADPH Oxidase activation are a well-known event in bioincompatibility phenomenon. NETs byproducts such as elastase, MPO and circulating DNA have been reported to be increased in dialysis patients more specifically during sessions and were identified as predictors of poor outcome. Since NETs and MPO could be taken up by endothelium, NETs could be considered as a vascular memory of intermittent bioincompatibility phenomenon. In this working hypothesis paper, we summarized the puzzle pieces showing the involvement of NET formation during hemodialysis and postulated that NETosis may act as a disease modifier and may contribute to the comorbid burden associated with dialysis bioincompatibility.